Penyuluhan Dalam Upaya Optimalisasi Tumbuh Kembang Anak Di Klinik Tumbuh Kembang Anak Joglo Jakarta Barat - Ulfa Diya Atiqa; Andi Hardianti; Syamsuriah, Syamsuriah; Rifhani Handayani L; Sri Gunda Fahriana Fahruddin (Saintify Publish, 2025)
Children are the hopes for the next generation for their parents. Therefore, it is essential to raise and care for them properly, while also closely monitoring their growth and development. Healthy growth and development aligned with their age will lead to the best outcomes. Issues in growth and development often arise when toddlers do not receive enough stimulation. This could be due to a lack of awareness among parents regarding the proper stimulation required at each stage of a toddler's growth and development. The method used aims to share information about children's growth and development through counseling. The target audience for this service activity is parents with children aged one to six years. As a result, the activities carried out aim to broaden knowledge, as well as parents' understanding and awareness of the importance of their children's growth and development.